The flow of information for project progress evaluation - Franco, Francisco Maravilla; Loo, Yew Chaye; Jearkjirm, Vithool; Ping Kunawatsdtit; OS-ASEAN Cooperation Programm (Bangkok : Asian Institute of Technology, 1984)
General and specific concepts on the design, implementation, and control of information systems , as applied in construction control and management , are presented in this paper. General concepts were derived from the literature of previous studies; leading to the development of a reference model of an information systems incorporated into the management and control system o a construction project. The presentation o f the reference model is supported by brief discussions on the systems objectives, design , implementation, and control. Specific concepts were d e rived from the investigation of on-going, reinforced-concrete, building constriction projects. The investigation was conducted through interviews, collection of sample forms, and observation; resulting to the identification of various applied models o t information system. The results of the investigation are presented herein and the discussions focus on the objectives of management, the information output, the raw data collected, forms used in information collection, processing, and presentation, and the procedures and forms used in the control of schedule, materials, and manpower at the site. Additional discussions are included emphasizing the importance of project meetings, wall charts, and verbal communications . The concepts presented in this paper are not directed towards a specific construction project nor toward a specific information system. which the reader is Rather, alternative concepts are given by aided in understanding information flow within the construction. Particularly, that part of the information flow leading to project progress valuation.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1984
Keywords: Construction industry -- Information storage and retrieval systems